Socioeconomic status and adiposity in childhood cancer survivors: A cross-sectional retrospective study - Štrublová, Lucie; Kepák, Tomáš; Kuruczová, Daniela; Zlámal, Filip; Holíková, Marta; Kepáková, Kateřina; Štěrba, Jaroslav; Bienertová-Vašků, Julie (PloS one, 2024)
This is a retrospective cross-sectional study examining the association between unemployment, cancer type, treatment and total body fat percentage of childhood cancer survivors recruited at St. Anne's University Hospital in Brno, Czech Republic. A total of 55 survivors aged 18-49 who were in remission of cancer and fulfilled the criteria for body composition measurements by the BIA and completed questionnaires investigating their socioeconomic status, employment status, and history. There was a significant relationship between the employment status and central nervous system-directed treatment (c2(1) = 7.53, p = 0.006, Cramér's V = 0.38) and between the type of cancer and employment status (c2(3) = 7.83, p = 0.049, Cramér's V = 0.38), the highest unemployment rate was recorded for brain and spine survivors (72.7%) compared to survivors with other diagnosis (35.7%) (uLR(1) = 4.91, p = 0.027; OR = 4.80, 95% CI:1.10-20.86, p = 0.036); these survivors did not have a significantly different body fat percentage compared to survivors with other diagnoses (t(53) = 1.29, p = 0.202, Cohen's d = 0.41) Interestingly, the survivors reporting having a partner also had a significantly higher percentage of body fat (t(53) = 2.90, p = 0.005, Cohen's d = 0.81). A linear regression model was used to model the percentage of body fat in relation to a set of selected variables and the we observed a significant effect of sex (female vs male: b = 6.37, 95% CI: 1.82-10.93, p = 0.007), partnership status (yes vs no: b = 5.65, 95% CI: 0.67-10.62, p = 0.027) and category of diagnosis (Brain and spinal column tumors vs Other solid tumors: b = 12.40, 95% CI: 0.59-24.21, p = 0.040; Brain and spinal column tumors vs Lymphoma: b = 14.02, 95% CI: 2.06-25.97, p = 0.023). Employment status and risk of adiposity in childhood cancer survivors depends on the type of treatment and diagnosis group, which may significantly impact their lifestyle and overall quality of life after treatment. Trial registration: This study was registered on July 29, 2022, at ClinicalTrials.gov (NCT05481229).
Keywords: nádory; Cross-Sectional Studies; retrospektivní studie; Humans; adipozita; Obesity; nádory centrálního nervového systému; kvalita života; Central Nervous System Neoplasms; mužské pohlaví; Cancer Survivors; přežívající onkologičtí pacienti; průřezové studie; ženské pohlaví; lidé; společenská třída; Neoplasms; dítě; Child; Adiposity; Quality of Life; Social Class; Male; Retrospective Studies; obezita; Female